1995
DOI: 10.1016/0014-5793(95)00233-y
|View full text |Cite
|
Sign up to set email alerts
|

An estimation of minimal genome size required for life

Abstract: The number of indispensable chromosomal loci for a bacterium, Bacillus subtilis was estimated. Seventy-nine randomly selected chromosomal loci were investigated by mutagenesis. Mutation at only six loci rendered B. subtilis unable to form colonies. In contrast, mutants for the rest of the 73 loci retained the ability to form colonies. Mutant B. subtilis with multiple-fold mutations of those dispensable loci (7-, 12-or 33-fold) were not impaired in their ability to form colonies on nutritionally adequate medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(67 citation statements)
references
References 13 publications
4
62
0
1
Order By: Relevance
“…These numbers are in agreement with the computational and experimental determinations of the minimal genome size necessary to sustain a functional cell (Itaya 1995;Mushegian and Koonin 1996;Pál et al 2006). However, the ancestral reconstruction of a minimal gene set in LUCA approaches are influenced by several factors.…”
Section: And What About Luca?supporting
confidence: 83%
“…These numbers are in agreement with the computational and experimental determinations of the minimal genome size necessary to sustain a functional cell (Itaya 1995;Mushegian and Koonin 1996;Pál et al 2006). However, the ancestral reconstruction of a minimal gene set in LUCA approaches are influenced by several factors.…”
Section: And What About Luca?supporting
confidence: 83%
“…lethal genes (Itaya, 1995). It did not list the essential genes but only their proportion regarding to the total number of genes.…”
Section: Experimental Approachmentioning
confidence: 99%
“…It was found in the 1990s that the number of truly essential genes of any organism might be quite small compared to its complete genome. For instance, some gene knock-out experiments have shown that the bacterium Bacillus subtilis might still do well with only ~300 genes left out of its original pool of ~4100 genes (Itaya 1995). Cross-species comparison of genomes via computational comparative genomics indicate that certain genes tend to be quite closely related across species.…”
Section: The 'Ancestral Organisms' and The Tree Of Life Before Themmentioning
confidence: 99%